ANALYSIS OF MATHEMATICS PROBLEM-SOLVING ABILITY BASED ON IDEAL PROBLEM-SOLVING STEPS GIVEN STUDENT LEARNING STYLES - Muhammad Isna Rosyada; Setiawan Edi Wibowo (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research aims to describe the mathematical problem-solving abilities of students with visual, auditory, and kinesthetic learning styles in solving sequence and series questions based on IDEAL problem-solving steps. In this study, the research method used is qualitative. Grouping students based on their learning style through a student learning style questionnaire, namely visual, auditory, and kinesthetic learning styles. Furthermore, data collection was carried out, namely holding a written test with sequences and series material. Then a problem-solving analysis was carried out from the answer data and interviews with the research subjects obtained. Data collection techniques used include Questionnaires, Tests, and Interviews. Meanwhile, in this study, the triangulation technique used is time triangulation. The results of the analysis and discussion show that students with a visual learning style have good abilities in solving mathematical problems. Students with a vimal learning style have no difficulty solving math problems based on the IDEAL Problem-Solving step. Meanwhile, students with auditory and kinesthetic learning styles could only carry out the first 2 steps of solving mathematical problems based on the IDEAL Problem-Solving step, namely the Identify Problem and Define Goal stages. From the research results, the following conclusions are obtained: First, in the type of visual learning style, students can carry out problem-solving based on the IDEAL Problem-Solving step well.